ASSESSING WORKFORCE READINESS FOR BLOCKCHAIN ADOPTION IN FOOD LOGISTICS: A CASE STUDY OF BULOG BANDUNG USING THE TRI 2.0 - Jasmine Budiyani; Yusep Sukrawan; Aulia Zikri Rahman (RADJA PUBLIKA, 2025)
The effectiveness and clarity of food logistics management, especially at BULOG Bandung, present notable challenges that call for the integration of blockchain technology. This research assesses the readiness of BULOG Bandung's workforce for the adoption of blockchain by utilizing the Technology Readiness Index (TRI) 2.0 framework. A quantitative research methodology was applied, which involved structured surveys and statistical analysis using Pearson correlation to evaluate employees' readiness. The results reveal a moderate level of technological readiness with an overall TRI score of 3.12. The dimensions of Optimism (3.42) and Innovativeness (3.25) suggest that employees possess a favorable view of technology, while Discomfort (2.92) and Insecurity (3.27) indicate apprehensions related to digital transformation. Analysis using Pearson correlation demonstrated a significant association between TRI dimensions and the willingness to adopt blockchain (r = 0.38, p < 0.05). These findings underscore the necessity for focused training initiatives, pilot blockchain projects, and technical assistance to boost employee confidence. Future investigations should examine the long-term behavioral adjustments and organizational elements that affect blockchain adoption in the logistics sector.